(untitled) (International journal of medical sciences, 2026)
Chronic Heart Failure (CHF) represents the final common pathway of various cardiovascular diseases and is a major public health concern in the Fergana Valley. This article presents a retrospective-prospective clinical study conducted at the Department of Faculty Therapy of Andijan State Medical Institute. Using the IMRAD framework, the research analyzes the etiological structure and risk factors contributing to the development of CHF in 84 patients residing in Andijan. The study evaluates the prevalence of ischemic heart disease (IHD), arterial hypertension (AH), and metabolic comorbidities. Results indicate that AH combined with IHD is the predominant etiological factor (65 percent), with a significant contribution from metabolic syndrome components. The study highlights the need for earlier intervention in the "pre-heart failure" stage within the local population.